A facile in situ Mg surface chemistry strategy for conditioning-free Mg[AlCl4]2 electrolytes. (10th May 2022) - Li, Xin; Liu, Qianqian; Wang, Xiaomian; Liu, Junjie; Cheng, Miao; Hu, Jing; Wei, Tao; Li, Wanfei; Ling, Yun; Chen, Bo; Pan, Zhenghui; Ma, Wujun; et al.
Highlights: A new conditioning-free Mg[AlCl4 ]2 -based Mg electrolyte is prepared. LiI additive enables an efficient Mg-ion-conducting interface. The symmetric cell with new electrolyte exhibits low overpotential. High performance of Mg/V2 O5 -PANi cell with new electrolyte is obtained. Abstract: Developing a simple and reliable strategy for modulating overpotential of Mg plating/stripping is crucial for realizing overall high performance of rechargeable Mg batteries, which have been demonstrated to be rather challenging. Herein, we report a facile LiI-assisted Mg surface chemistry to reduce Mg plating/stripping overpotential via in situ solubilization mechanism and ion conductive surface layer formation mechanism. As a result, we successfully formulate a new conditioning-free Mg[AlCl4 ]2 -based Mg electrolyte system that improves Mg plating/stripping from the very first cycle. The overpotential of Mg plating/stripping of the as-prepared electrolyte with a LiI electrolyte additive is remarkably reduced to 240/240 mV at a current density of 1000 µA cm −2 . Using this electrolyte, a rechargeable Mg battery coupled with PANi intercalated V2 O5 (V2 O5 -PANi) cathode and Mg anode delivers a stable discharge specific capacity of nearly 50 mA h g −1 after an impressively prolonged cycle life of 500 cycles. Our finding provides a new inspiration of in situ Mg surface chemistry to activate Mg anode surface with high Mg ion conductivity. Graphical abstract: Image, graphical abstract A Conditioning-Free LiI-added Mg[AlCl4 ]2 Electrolyte is developed with enhanced Mg plating/stripping from the first cycle. The performance of the as-prepared electrolyte shows a low Mg plating/stripping overpotential of 240/240 mV at a current density of 1000 µA cm −2, a long cycle stability over 500 cycles and good rate capacity for rechargeable Mg/V2 O5 -PANi cell.